Integrasi Sejarah Lokal Pada Bahan Ajar Mata Pelajaran Sejarah Indonesia - Siti Nurhima Yustira; Ridho Bayu Yefterson (Jurnal Kronologi, 2021)
Abstract Ideally, history learning can make students have historical thinking skills, which in this case also includes change thinking. The reality is that in the field these skills are still not mastered by students. There are many ways to make history learning more meaningful and interesting. Among the many ways, one that can be done is to integrate local historical material and then add various image media in it. The objectives of this study include (1) to describe the stages of developing Indonesian history teaching materials by integrating local history at SMAN 1 Lareh Sago Halaban and (2) to describe the feasibility (validity) of Indonesian history teaching materials by integrating local history at SMAN 1 Lareh. Sago Halaban. This research uses research and development or R&D methods. In developing teaching materials with the integration of local history, the researchers used the ADDIE model which was cut into ADD (Analysis, Design, and Development). This limitation is due to limited time and research funds. The results of this study include (1) In making the product, the first step is to analyze several aspects, including analyzing the needs of students, teachers and curriculum, (2) After that, elaborating various sources by emphasizing the truth of facts, concepts and principles to be used as material. teaching materials in teaching materials products with the integration of local history, (3) The development phase validates by material experts and teaching materials experts. Keywords: History Learning, Teaching Materials, Historical Thinking, Change Thinking, Local history